Literature, immigration and diaspora in fin-de-siecle England : a cultural history of the 1905 Aliens Act - Glover, David , 1946- (Cambridge University Press, 2012)
"The 1905 Aliens Act was the first modern law to restrict immigration to British shores. In this book, David Glover asks how it was possible for Britain, a nation that had prided itself on offering asylum to refugees, to pass such legislation. Tracing the ways that the legal notion of the 'alien' became a national-racist epithet indistinguishable from the figure of 'the Jew', Glover argues that the literary and popular entertainments of fin de siècle Britain perpetuated a culture of xenophobia. Reconstructing the complex socio-political field known as the alien question', Glover examines the work of George Eliot, Israel Zangwill, Rudyard Kipling and Joseph Conrad,together with forgotten writers like Margaret Harkness, Edgar Wallace and James Blyth. By linking them to the beliefs and ideologies that circulated via newspapers, periodicals, political meetings, Royal Commissions, patriotic melodramas and social surveys, Glover sheds new light on dilemmas about nationality, borders and citizenship"-- Provided by publisher